2022
DOI: 10.3389/fcvm.2021.781157
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features of Patients Undergoing the Head-Up Tilt Test and Its Safety and Efficacy in Diagnosing Vasovagal Syncope in 4,873 Patients

Abstract: Background: The head-up tilt test (HUTT) is a useful diagnostic tool in patients with suspected vasovagal syncope (VVS).Objectives: We aimed to investigate the direct drug-potentiated HUTT in patients with recurrent syncope or precursor syncope and to assess the diagnostic value of the direct drug-potentiated HUTT.Methods: The medical history and direct drug-potentiated HUTT records of patients who complained of syncope or precursor syncope and who visited The Xianyang Central Hospital from January 2016 to Dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
(30 reference statements)
0
0
0
Order By: Relevance
“…In a study done by Xu et al [14] 4873 patients with reflex syncope underwent tilt table test after provocation by sublingual nitroglycerine, this study results concluded that patients who had syncope showed increased heart rate during tilting then decreased at the time of syncope associated with decreased blood pressure which agreed with our results.…”
Section: Discussionsupporting
confidence: 91%
“…In a study done by Xu et al [14] 4873 patients with reflex syncope underwent tilt table test after provocation by sublingual nitroglycerine, this study results concluded that patients who had syncope showed increased heart rate during tilting then decreased at the time of syncope associated with decreased blood pressure which agreed with our results.…”
Section: Discussionsupporting
confidence: 91%
“…In a previous study, similar results were found, with dizziness being the most common indication for undergoing HUTT. 14 According to our study, apart from dizziness, we did not find any significant correlation between presenting symptoms, age, sex, and outcomes of HUTT. This is synchronous with the reported findings of other investigators who performed similar studies.…”
Section: Discussioncontrasting
confidence: 56%